Reappraising Durkheim for the Study and Teaching of Religion Today. - Idinopulos; Brian C. Wilson (Editors) (Numen Book Series, 2002)
Reappraising Durkheim for the Study and Teaching of Religion Today is an occasion to critically analyze and reassess the work of this intellectual pioneer. It is also an effort to signal the continuing importance of Durkheim for today's graduate and advanced undergraduate classrooms. Reappraising Durkheim brings together ten new critical essays in which noted sociologists, psychologists, phenomenologists, philosophers, and historians of religion grapple with the questions Durkheim raised and the solutions he proposed. Taken together, the volume is a careful historical and multi-disciplinary study of Durkheim that will lead students to a better understanding of how to study religion. Reappraising Durkheim will be an excellent text for courses focusing on theory and method in the academic study of religion at both the graduate and advanced undergraduate level. It would therefore be appropriate for use in departments of religious studies, philosophy, sociology, and anthropology.